Constitutional action to protect the right to social security - Bonilla Alarcón, Luís Alfonso; Cabrera Vélez, Juan Pablo; Ruiz Abril, Karina Marianela (Revista Universidad de Guayaquil, 2018)
Within the present work we will have to deal with: "The constitutional action to protect the right to social security." Due to the fact that social security is guaranteed in Ecuador, in practice there are problems in its exercise, as it is the case of intentionally reducing the payment corresponding to retirement, with the clear intention of avoiding employer responsibility. Another Ecuadorian experience that should be mentioned is that the social security institutions are reluctant to provide the hospital service that is owed by law to the family of the insured. In the face of these events, it has been necessary for the Constitutional Court to issue sentences compelling compliance with social security, so this work will refer to the experience that exists on this matter.The methodology to be used in the research is deductive, exploratory and descriptive. A qualitative approach will be used, as it is the one of the social sciences and more punctually of the Law.
Keywords: Constitutional law; constitutional action; social security; solidary system; effective protection